2019
DOI: 10.25105/urbanenvirotech.v0i0.4364
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Recharge for Sustainable Groundwater Management Plan in Yogyakarta

Abstract: <strong>Aim: </strong>This study investigates the development of a sustainable groundwater management strategy in Yogyakarta province through groundwater recharge technologies. This study also compares technologies used in the province and the one already implemented in Perth due to its similar nature in site geology and hydrogeology. <strong>Methodology and Results: </strong>Primary and secondary data were collected and analyzed. Water depth and hydraulic conductivity data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The increase in population has resulted in high groundwater abstraction, but it did not jeopardize the groundwater balance and the groundwater level of Yogyakarta City [6]. On the other hand, recent papers on groundwater quality in Yogyakarta Province have shown a few issues regarding the pollution risk potential in Yogyakarta City [7], and groundwater management in Yogyakarta Province [8]. A study also identified the temporal variation of groundwater quality and nitrate and manganese elevated concentration in the Sleman District of Yogyakarta Province [9].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in population has resulted in high groundwater abstraction, but it did not jeopardize the groundwater balance and the groundwater level of Yogyakarta City [6]. On the other hand, recent papers on groundwater quality in Yogyakarta Province have shown a few issues regarding the pollution risk potential in Yogyakarta City [7], and groundwater management in Yogyakarta Province [8]. A study also identified the temporal variation of groundwater quality and nitrate and manganese elevated concentration in the Sleman District of Yogyakarta Province [9].…”
Section: Introductionmentioning
confidence: 99%
“…32 [4] has set quality standards for groundwater quality for sanitation hygiene needs that must include physical, biological, and chemical parameters. Knowing the distribution of groundwater quality in urban cities is an informative tool in the form of a geographic information system (GIS) as an effective way to represent and analyze spatial data on water resources [5,6]. So that the mapping results in the form of a spatial map will describe the water quality categories found in the entire study area [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, water resources must be managed properly so that the availability of water can be sufficient. Well-managed water resources can ensure the availability and sustainability of water in water source [5,6,7].…”
Section: Introductionmentioning
confidence: 99%